Amelogenin Downregulates Interferon Gamma-Induced Major Histocompatibility Complex Class II Expression Through Suppression of Euchromatin Formation in the Class II Transactivator Promoter IV Region in Macrophages - Yotsumoto, Karen; Sanui, Terukazu; Tanaka, Urara; Yamato, Hiroaki; Alshargabi, Rehab; Shinjo, Takanori; Nakao, Yuki; Watanabe, Yukari; Hayashi, Chikako; Taketomi, Takaharu; Fukuda, Takao; Nishimura, Fusanori (Frontiers in Immunology, 2020)
Enamel matrix derivatives (EMDs)-based periodontal tissue regenerative therapy is known to promote healing with minimal inflammatory response after periodontal surgery, i.e., it promotes wound healing with reduced pain and swelling. It has also been reported that macrophages stimulated with amelogenin, a major component of EMD, produce various anti-inflammatory cytokines and growth factors. We previously found that stimulation of monocytes with murine recombinant M180 (rM180) amelogenin suppresses major histocompatibility complex class II (MHC II) gene expression using microarray analysis. However, the detailed molecular mechanisms for this process remain unclear. In the present study, we demonstrated that rM180 amelogenin selectively downmodulates the interferon gamma (IFNγ)-induced cell surface expression of MHC II molecules in macrophages and this mechanism mediated by rM180 appeared to be widely conserved across species. Furthermore, rM180 accumulated in the nucleus of macrophages at 15 min after stimulation and inhibited the protein expression of class II transactivator (CIITA) which controls the transcription of MHC II by IFNγ. In addition, reduced MHC II expression on macrophages pretreated with rM180 impaired the expression of T cell activation markers CD25 and CD69, T cell proliferation ability, and IL-2 production by allogenic CD4+ T lymphocytes in mixed lymphocyte reaction assay. The chromatin immunoprecipitation assay showed that IFNγ stimulation increased the acetylation of histone H3 lysine 27, which is important for conversion to euchromatin, as well as the trimethylation of histone H3 lysine 4 levels in the CIITA promoter IV p-IV) region, but both were suppressed in the group stimulated with IFNγ after rM180 treatment. In conclusion, the present study shows that amelogenin suppresses MHC II expression by altering chromatin structure and inhibiting CIITA p-IV transcription activity, and attenuates subsequent T cell activation. Clinically observed acceleration of wound healing after periodontal surgery by amelogenin may be partially mediated by the mechanism elucidated in this study. In addition, the use of recombinant amelogenin is safe because it is biologically derived protein. Therefore, amelogenin may also be used in future as an immunosuppressant with minimal side effects for organ transplantation or MHC II-linked autoimmune diseases such as type I diabetes, multiple sclerosis, and rheumatoid arthritis, among others.